Building a personal brand on social media - Curtis, Robin; Král, Petr, 1979-; Zlatić, Marija; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
This bachelor thesis analyses branding techniques for the creation of strong brand equity and a cohesive brand identity for individuals seeking to use social media in order to generate revenue through a personal brand. The purpose of this work is to create a personal brand on social media for myself with the use of theoretical knowledge gained throughout the thesis. The first part examines how leading branding experts create brand equity and a strong brand identity in order to create loyal customers. The second part takes a look at personal branding, contrasting it to that of corporate branding and analyses methods how individuals can differentiate themselves and use social media to create brand trust, brand visibility and revenue generating streams. The practical part of the thesis is dedicated to defining and creating a cohesive personal brand and the monetisation opportunities for myself.
Vedoucí práce: Petr Král
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses